A new binary particle swarm optimizer to select a smaller subset of genes for leukaemia cancer classification - Mohamad, Mohd. Saberi; Omatu, Sigeru; Deris, Safaai; Yoshioka, Michifuci; Zainal, Anazida (Penerbit UTM Press, 2008)
The application of microarray data for cancer classification has recently gained in popularity. The main problem that needs to be addressed is the selection of a smaller subset of genes from the thousands of genes in the data that contributes to a disease. This selection process is difficult because of the availability of the small number of samples compared to the huge number of genes, many irrelevant genes, and noisy genes. Therefore, this paper proposes an improved binary particle swarm optimization to select a near-optimal (smaller) subset of informative genes that is relevant for cancer classification. Experimental results show that the performance of the proposed method is superior to the experimental method and other related previous works in terms of classification accuracy and the number of selected genes.